Plan estrategico de marketing de la marca de la Optica “Solvision del canton Babahoyo, periodo 2022. - Filian Burgos, Katherine Ivonne (2023)
SolVision opticians is a company dedicated to the service of visual diagnostics and the sale of glasses and contact lenses with measurements, it is located in the city of Babahoyo. It has remained in the market despite the competitions that have caused a decrease in the positioning of its brand and has become problematic. For this reason, this case study has been carried out with the objective of creating a Strategic Marketing Plan to increase the positioning of the company's Brand. The Marketing strategies that must be carried out for the brand to be recognized are: Creation of a website, social networks (Facebook, Instagram), dissemination in WhatsApp groups, rolling advertising, billboards. The implementation of Digital Markerting will generate better communication and greater reliability with the company and its clients and will also provide a quick service when providing answers and concerns on its web pages. Through these social network links, the goal is for the customer to obtain more information about the products offered by the company and thus create loyalty in its customers.